Please forget democracy and justice: Eritrean politics and the powers of humor. (10th May 2013) - Bernal, Victoria
ABSTRACT: Parody possesses a kind of power that realist critique sometimes lacks. I explore why humor is sometimes used as a medium for addressing tragic circumstances and why parody in particular may be especially suited to communicating about dictatorship. The research presented here draws on a long‐term project on Eritrean politics and on websites devoted to Eritrean politics created by Eritreans in diaspora. The core of the analysis dissects an online political parody of conditions under the regime of President Isaias Afewerki. So much of what is known and written about Eritrean history and current realities, whether by scholars, journalists, international organizations, or Eritreans online, is earnest, serious, and even heartbreaking. The uses of humor in this context seem to call for an explanation, and the analysis presented here sheds light on the mechanisms through which humor accomplishes important political work and fosters the development of new subjectivities.